P167 Outcomesand Predictors Of Mortality In Cancer Patients With Incidental Pulmonary Embolism. (10th November 2014) - Grant, D; Franklin, J; Watts, L; Rahman, N; Gleeson, FV
Abstract : Objectives: Incidental pulmonary emboli (iPE) are detected in a significant minority of contrast CT scans performed during the management of patients with cancer. These patients are reported to have an increased mortality compared to matched controls. This study investigates outcomes and predictors of mortality following iPE. Methods: Reports of all contrast-enhanced CT scans including the chest, excluding dedicated CT pulmonary angiography, performed between 1st May 2012 and 30th September 2013, were searched for prospectively identified iPE. Clinical data was collected from multiple sources, including clinic letters, discharge summaries, and the hospital patient database. Patients presenting with acute symptoms consistent with PE or those already receiving therapeutic anticoagulation were excluded. Potential clinical and radiological predictors of mortality were defined pre-hoc and tested using Student's t-test and Cox proportional-hazard regression. Results: There were 160 cancer patients with iPE. Anticoagulation treatment was given in 97% of cases. Overall 30-day and 6-month mortality following iPE was 20.6% (95% confidence interval 15.0–27.6%) and 52.5% (44.8–60.1%), respectively. Increased 30-day and 6-month mortality was observed in scans performed on inpatients compared to outpatients (38.2% vs 11.4%, p = 0.0004 and 78.2% vs 40.0%, p < 0.0001). 6-month mortality was also increased if this was a new diagnosis of malignancy at the time of the CT scan compared to patients with known malignancy (69.4% vs 46.0%, p = 0.0046), or if metastases were present at the time of CT scan (58.3% vs 26.7%, p = 0.0012). There were 86 (53.8%) central (main or lobar pulmonary arteries), 60 (37.5%) segmental, and 14 (8.8%) subsegmental pulmonary emboli. No significant mortality difference was observed between these radiological features. Conclusion: This study has assessed potential poor prognostic features in patients with cancer and iPE. Despite the vast majority receiving therapeutic anticoagulation, there is a high 30-day and 6-month mortality. The benefits of conventional treatment in this clinical situation are as yet unclear.